Endoscopic injection sclerotherapy under red dichromatic imaging for esophageal varices. Issue 3 (9th February 2022) - Hikichi, Takuto; Nakamura, Jun; Kato, Tsunetaka; Hashimoto, Minami; Kobashi, Ryoichiro
Abstract : This Editorial refers to the article by Y. Furuichi et al., p 87‐95 of the issue DEN 34:1.